Transposon-tagging identifies novel pathogenicity genes in Fusarium graminearum - Dufresne, M.; Van Der Lee, T.; M'Barek, S.B.; Xu, X.; Zhang, X.; Liu, T.; Waalwijk, C.; Waalwijk, C.; Kema, G.H.J.; Daboussi, M.J.
With the increase of sequenced fungal genomes, high-throughput methods for functional analyses of genes are needed. We assessed the potential of a new transposon mutagenesis tool deploying a Fusarium oxysporum miniature inverted-repeat transposable element mimp1, mobilized by the transposase of impala, a Tc1-like transposon, to obtain knock-out mutants in Fusarium graminearum. We localized 91 mimp1 insertions which showed good distribution over the entire genome. The main exception was a major hotspot on chromosome 2 where independent insertions occurred at exactly the same nucleotide position. Furthermore insertions in promoter regions were over-represented. Screening 331 mutants for sexual development, radial growth and pathogenicity on wheat resulted in 19 mutants (5.7
Keywords: TRANSPOSON MUTAGENESIS; FUSARIUM GRAMINEARUM; FUNCTIONAL SCREENING; PATHOGENICITY; SEXUAL DEVELOPMENT